Indoor living environments: The VITALITY project in the Marche region (Italy) – integrating sensors and utilities for climatic-environmental monitoring to promote human health - Paniccià, Marco; Acito, Mattia; Grappasonni, Iolanda (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: The integration of sensor-based systems in living environments and microenvironments, both indoor and outdoor, represents a brilliant approach for the continuous and real-time collection of data on climatic-environmental variables (such as air temperature, relative humidity, air velocity, volatile organic compounds, and CO₂). These data are instrumental in supporting decision-making processes to prevent and mitigate negative environmental impacts, particularly in highly vulnerable urban contexts. Methods: This paper outlines the research design, objectives, and progress of the Italian PNRR VITALITY Project, SPOKE 6, WP 1.4, titled “Well-being Conditions Between Indoor and Outdoor Spaces”. Specifically, the study focuses on an in-depth analysis of selected indoor climatic-environmental variables that influence human health. Environmental data will be acquired through sensors, processed, and recorded on a digital platform, and integrated into a utility designed for users in three experimental investigation areas (three distinct urban contexts in central Italy, within the Marche Region). Results: Operational phases are scheduled to commence by the end of 2025. Conclusions: This type of monitoring enables a deeper and context-specific understanding of environmental conditions, providing essential information for the analysis of risk factors and the safeguarding and promotion of well-being and health (www.actabiomedica.it).